(untitled) (Anwer Khan Modern Medical College Journal, 2012)
This experimental study was done to determine whether Ganoderma Lucidum (GL), a renowned medicinal species, has an effect on body weight in an obese animal model induced by the administration of a fatty mixture diet. The study was carried out in the department of Pharmacy, Jahangirnagar University and National Mushroom Development and Extension Center (NAMDEC) with 36 rats were divided into 3 groups as follows. The Control group (C) received normal/basal laboratory diet, experimental group (E) was fed fatty mixture diet and mushroom fed group (M) received 5% powder of GL with fatty mixture for 28 days. 5% powder of GL administration significantly reduced body weight in obese rats than group E. The present study suggests that GL may serve as a new potential natural product for the prevention of obesity. DOI: http://dx.doi.org/10.3329/akmmcj.v3i2.11687 AKMMC J 2012: 3(2): 11-14